Integrasi Agama dan Sains dalam Perspektif M. Naquib al-Attas: Relevansinya dalam Pengembangan Pendidikan Islam Kontemporer - Syaybatul Afni; Ma’isyah, Roza; Amril M; Liana Novita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The thought of Syed Muhammad Naquib al-Attas emphasizes the integration of religion and science through the concept of ta'dib (religious guidance) and the monotheistic worldview, which rejects the dichotomy of knowledge. This study aims to analyze this idea and its relevance in contemporary Islamic education using a literature study method. The results indicate that this integration is crucial for addressing the secularization of knowledge and the moral crisis, through the development of a monotheistic-based curriculum and the strengthening of adab (good manners). Thus, Al-Attas' concept is relevant in building a holistic and character-based Islamic education.